Strategi Penurunan Angka Stunting dan Analisis Hambatan Kebijakan - Wynne Frederica; Laila Khalid Al-Firdaus; Fitriyah Fitriyah (CV. Lenggogeni Data Publishing, 2024)
Stunting has been proven to be a global issue that significantly impacts the growth of a country. In Indonesia, the problem of stunting has become one of the Strategic Priority Projects (Major Projects) in the National Medium-Term Development Plan 2022-2024. Based on this decision, each regents, including Kendal Regency, has also been promoting the acceleration of stunting reduction. Various medical studies have extensively discussed the dangers, factors, and the actions that can be undertaken to prevent stunting. However, they have yet to elaborate on the actual obstacles faced by local governments in their efforts to create stunting-free regions. The purpose of this study is to identify strategies for reducing stunting and the factors that may hinder the achievement of stunting reduction targets. In collecting research data, the author uses a qualitative descriptive method obtained from literature reviews, observations, and interviews involving relevant stakeholders.